Preparation and Stability of Deep Eutectic Solvent Based Nanofluids as a Future Heat Transfer Fluid – A Review - Mior Ahmad Nazhan Mior Afendi; Muhammad Arif Ammar Rohazien; Syukrina Imtiyaz Abdul Samat (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan